Melflufen for the treatment of multiple myeloma. Issue 4 (3rd April 2022) - Ocio, Enrique M.; Nadeem, Omar; Schjesvold, Fredrik; Gay, Francesca; Touzeau, Cyrille; Dimopoulos, Meletios A.; Richardson, Paul G.; Mateos, Maria-Victoria
ABSTRACT: Introduction: Melphalan flufenamide (melflufen) is a first-in-class peptide–drug conjugate that takes advantage of increased aminopeptidase activity inside tumor cells to rapidly release alkylating agents therein. Melflufen in combination with dexamethasone has been evaluated in multiple clinical trials in patients with relapsed/refractory multiple myeloma (MM). Areas covered: This profile covers the unique mechanism of action of melflufen, the preclinical results supporting its activity in cellular models of resistance to chemotherapy, its activity in animal models of MM, and the clinical pharmacokinetics of melflufen. Findings from clinical trials evaluating melflufen, including the pivotal phase II HORIZON study and the phase III OCEAN study, are discussed. Expert opinion: Although MM treatment has improved, patients with disease refractory to multiple standard-of-care drug classes face a dismal prognosis. Melflufen demonstrated efficacy and tolerability in select populations, with an initial approval in the United States in patients with ≥ four previous lines of therapy and triple-class-refractory MM. Results from the phase III OCEAN study – currently under discussion with regulatory agencies in the United States and Europe – are more complex and have been put into context herein. Lastly, melflufen provides a proof-of-concept for the utility of the peptide–drug conjugate platform in relapsed/refractory MM.